Trends in Polish agriculture in the 30-year period of 1990–2019 - Harasim, Adam; Matyka, Mariusz (Polish Journal of Agronomy, 2021)
Presented paper analyzed changes in Polish agricul- ture assessed on the basis of 22 indicators characterizing agricul- tural resources, consumption of production goods and the result of agricultural production in the years 1990–2019. The aim of the research was to find the trends that have emerged in Polish agriculture in the last 30 years. The data published by the Cen- tral Statistical Office was used as source data. The results showed a significant dynamics of changes in both level and structure of agricultural production. Since 1990s, the specialization of farms has deepened, which was a result of the systemic transformation and Poland’s acces- sion to the structures of the European Union. The specialization was deepened mostly through the changes in use of production factors to promote the leading agricultural activity of farm in terms of increasing the scale and marketability of production. The study showed some positive changes of Polish agriculture, i.e.: the development of large farms, an increase in the average area of farms and in land concentration, increased yields of plants, slaughter efficiency of livestock and milk efficiency of cows, re- duction of employment in agriculture as a factor of increasing la- bor productivity. On the other hand, the unfavorable phenomena were found, such as: decreasing acreage of agricultural land in Poland, reduction of outlays on certain production goods (includ- ing low use of certified seeds and fertilizing lime), a downward trend in the number of livestock (but with a noticeable improve- ment in their productivity). The main determinants of changes in the level and structure of agricultural production included a reduction in the area of ag- ricultural land and the number of commercial farms, as well as an increase in their average area, but also an increase in plant and livestock production efficiency.